Genetic and pharmacologic p32-inhibition rescue CHCHD2-linked Parkinson’s disease phenotypes in vivo and in cell models - Murni Tio; Rujing Wen; Cai Ning Choo; Jian Bin Tan; Aaron Chua; Bin Xiao; Jeyapriya Rajameenakshi Sundaram; Christine Hui Shan Chan; Eng-King Tan (Journal of Biomedical Science, 2024)
Abstract Background Mutations in CHCHD2 have been linked to Parkinson’s disease, however, their exact pathophysiologic roles are unclear. The p32 protein has been suggested to interact with CHCHD2, however, the physiological functions of such interaction in the context of PD have not been clarified. Methods Interaction between CHCHD2 and p32 was confirmed by co-immunoprecipitation experiments. We studied the effect of p32-knockdown in the transgenic Drosophila and Hela cells expressing the wild type and the pathogenic variants of hCHCHD2. We further investigated the rescue ability of a custom generated p32-inhibitor in these models as well as in the human fibroblast derived neural precursor cells and the dopaminergic neurons harboring hCHCHD2-Arg145Gln. Results Our results showed that wildtype and mutant hCHCHD2 could bind to p32 in vitro, supported by in vivo interaction between human CHCHD2 and Drosophila p32. Knockdown of p32 reduced mutant hCHCHD2 levels in Drosophila and in vitro. In Drosophila hCHCHD2 models, inhibition of p32 through genetic knockdown and pharmacological treatment using a customized p32-inhibitor restored dopaminergic neuron numbers and improved mitochondrial morphology. These were correlated with improved locomotor function, reduced oxidative stress and decreased mortality. Consistently, Hela cells expressing mutant hCHCHD2 showed improved mitochondrial morphology and function after treatment with the p32-inhibitor. As compared to the isogenic control cells, large percentage of the mutant neural precursor cells and dopaminergic neurons harboring hCHCHD2-Arg145Gln contained fragmented mitochondria which was accompanied by lower ATP production and cell viability. The NPCs harboring hCHCHD2-Arg145Gln also had a marked increase in α-synuclein expression. The p32-inhibitor was able to ameliorate the mitochondrial fragmentation, restored ATP levels, increased cell viability and reduced α-synuclein level in these cells. Conclusions Our study identified p32 as a modulator of CHCHD2, possibly exerting its effects by reducing the toxic mutant hCHCHD2 expression and/or mitigating the downstream effects. Inhibition of the p32 pathway can be a potential therapeutic intervention for CHCHD2-linked PD and diseases involving mitochondrial dysfunction.